Clinical and dermoscopic features associated with lichen planus-like keratoses that undergo skin biopsy: a single-center, observational study - Liopyris, Konstantinos (Australas J Dermatol, 2018)
BACKGROUND / OBJECTIVES: Lichen Planus-like Keratoses (LPLKs) are benign skin lesions that can mimic malignancy; the clinical and dermoscopic features distinguishing LPLKs from skin tumors have not been extensively studied. The objective of this study was to identify dermoscopic features that may prevent unnecessary biopsies of LPLKs. METHODS: Retrospective, observational study of biopsied skin lesions. We compared 355 LPLKs to 118 non-LPLK lesions with LPLK in the differential diagnosis biopsied from August 1, 2015, to December 31, 2016. The investigators were blinded to the diagnosis of the lesions. A single-centre, observational study in a tertiary centre. RESULTS: LPLKs were most frequently non-pigmented (61.7%), truncal (52.1%), and on sun-damaged skin (69.6%); the majority occurred in Whites (95.5%) and females (62.8%). Dermoscopically, LPLKs were more likely than non-LPLKs to have scale (42.5% v. 31.4%, p=0.03) and orange color (8.2% v. 0.9%, p=0.01). Among lesions with peppering (n=76; 63 LPLK and 13 non-LPLK, coarse ± fine peppering (73% v. 38.5%, p=0.02) and peppering as the only feature (34.9% v. 0%, p=0.01) were associated with LPLK. CONCLUSIONS: LPLKs can be challenging to distinguish from benign and malignant skin tumors. The presence of dermoscopic scale and orange color may aid in the recognition of LPLK. Coarse peppering and the presence of peppering as the only dermoscopic feature may further aid the identification of pigmented LPLKs.